Structure and semantic peculiarities of founa- and floranymies at the morden Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article investigates the question of depening the structure and semantic of constructions of possessiveness on the possessivene constituents. It also examines in defining the transformational models of possessivene units.
Keywords: possession; semantic constituent of possessive connection; transformational analysis